A Review of Critical Success Factors (CSFs) For Executive Information System (EIS) Development in Education Domain - Mahamsiatus Kamaruddin (Pejabat Karang Mengarang UPSI, 2017)
This study reviews the critical success factors (CSFs) of executive information systems (EIS) development for education domain. EIS is the information system that can integrate internal and external information, which allows executives formulate plans, explain the indicators, determine organisation performance, mapping productivity and make strategic decision making. Although the implementation of the EIS can be complying using the standard system development life cycle (SDLC) model, the CSFs that affect its development is important to identify to the success of its initiative. Previous studies have examined various CSF to the success of EIS implementation, but explanation the significant of CSF based on the findings in education EIS development needs to discuss further. The study was accomplished through content analysis approaches based on the previous findings on CSF framework in education EIS development study done by the author. The results explained the review of CSF components discovered, (1) organisational contexts, (2) human resources, (3) development activities, and (4) EIS as a product. These findings potentially used as a reference to the continuing development of education EIS or the development of EIS in any organisation that possess management background similar as an education field.